Development of a model of the optimal temperature mode of the main gas pipeline operation - Kologrivov, Mykhail; Buzovskyi, Vitalii (Eastern-European Journal of Enterprise Technologies, 2021)
The influence of the ambient air temperature on changes in the parameters and thermophysical characteristics of the gas pumped through the underground pipeline was investigated. This was done because there are no scientifically sound recommendations for the optimal gas temperature after coolers at the compressor station. The presence of the site of inversion of heat exchange between gas and soil – a change in the direction of heat exchange along the length of the gas pipeline was revealed. It was proved that the air temperature above the soil surface should be substituted into the formula for calculating the change in gas temperature along the length of the pipeline between compressor stations. This made it possible to determine quantitative changes in the thermophysical and hydraulic characteristics of the gas along the pipe length, in particular, the change in density, viscosity, heat capacity, flow regime. It is shown that the change in air temperature during the year leads to a change in the gas pressure at the end of the gas pipeline section up to 0.15 MPa. A change in air temperature by 10 °С leads to a change in gas temperature by approximately 5 °С. Analytical studies made it possible to develop practical recommendations for the power-saving operation of air coolers at compressor stations. It was determined that the optimum gas temperature at the cooler outlet will be the temperature at which the heat exchange inversion point along the length of the gas pipeline coincides with the location of the subsequent station. It is shown how to control gas cooling in air coolers. In particular, by shutting down one of several operating devices and changing the speed of the fan drive. The developed recommendations will make it possible to quickly regulate the temperature mode of the underground gas pipeline operation at optimal power consumption for the operation of the gas cooling system after gas compression